Patriarchy Meat. Animal-Female Consumption in Three Recent Feminist Dystopias: Cadáver exquisito by AgustinaBazterrica, Nación Vacuna by Fernanda García Lao and Sirènes by Laura Pugno (Anclajes, 2024)
Three recent dystopian novels written by women explore the links between the consumption and exploitation of animal meat and the female body: Cadáver exquisito (2017), by the Argentine writer Agustina Bazterrica; Nación Vacuna (2017), by the Argentine writer Fernanda García Lao; and Sirènes (2007), by the Italian writer Laura Pugno. In these, the links between the consumption and the exploitation of animal meat and the female body reveal the use of female bodies in their reproductive capacity as meat at the service of patriarchy. Thus, in this paper, we will analyze, first, the connections between animal meat and the female body; then, the reproductive exploitation of the female body, to conclude on the similarities and differences between the works.
Keywords: Feminist Dytopia; Consumption/exploitation; Animal Meat; Female Body; Reproduction